Management accounting and control in higher education institutions: A systematic literature review - José Vale; Joana Amaral; Luís Abrantes; Carmem Pereira Leal; Rui Silva (Administrative Sciences, 2022)
The new public management reforms have led to significant changes in higher education institutions (HEIs) regarding the management accounting and control (MAC) of these organizations. Therefore, this paper provides an overview of the main studies on MAC in these types of organizations through a systematic literature review (SLR). The PRISMA guidelines were followed, and data were collected from the Web of Science and Scopus databases. The final sample encompassed 50 articles, published between 1981 and 2020. The results show that MAC research tends to focus on management control systems and performance evaluation systems. They also suggest that, although the development and implementation of various MAC tools are crucial for HEIs, such implementation often is partial. This is due to the stakeholders' perceptions/attitudes regarding the importance of such tools. The results also indicate that institutional theory is the most addressed one. Most of the time, HEIs implement MAC tools due to external pressures. By synthesizing the main trends in MAC, this SLR intends to provide a theoretical contribution to the literature in this research field. Several themes for further research are suggested, such as assessing the relationship between MAC and the management of "knowledge" and intellectual capital in these institutions, and addressing sustainability issues. From a practical viewpoint, HEI managers can obtain important insights to apply the most appropriate tools to their institutions.
Keywords: 350; accounting theories; higher education institutions; management accounting; management control; systematic literature review